RESTORATIVE ARCHITECTURE Designing for mutually supportive systems - Hansten, Alexandra; Ekström, Sara (My University, 2023)
This thesis addresses the urgent need for a shift in how architecture relates to natural resource extraction in the face of the twin crises of climate breakdown and biodiversity loss. The aim of this thesis is to explore a system that responds to the twin crisis by sourcing biomass as rest products from ecologically restorative processes and implementing them as regenerative building materials. The purpose behind this is to highlight the architects’ possibility of executing a holistic practice where our systemized approach to problem solving holds the potential to respond to complex societal issues. The research focuses on coastal environments and covers three bioremediating marine species; blue mussels, reeds, and eelgrass, whose biological functions naturally help counteract eutrophication. The studies of these species result in a mapping of their biological function, occurrence, physical properties, and potential to perform as building materials. Traditional and modern case studies, interviews, and literature studies are used to support the research. The thesis re-connects to the pressing issue of the twin crisis in the design phase where both program and building reflects and promotes a sustainable relationship between natural resources and human consumption in the rurban setting of Stora Dyrön. More specifically, the new addition contains a program that answers to an uneven seasonal activity by extending the tourism season through a sustainable experience-based restaurant that cultivates marine species through a local, small scale blue garden. The outcome of this thesis provides insights in the possibilities and challenges with connecting material extraction to nature restoration. This has been done through the holistic approach of making visible systems and connections across different scales. It concludes that this practice would pose demands on the building sector in terms of attitudes, material sourcing and craftmanship. This would in contrast to todays linear resource use, depart from available supply rather than material demand where the environmental benefit of bio-based materials has to be elevated. By acknowledging that architects’ systemized approach to problem solving could help tackle complex societal issues, and openess to cross-disciplinary collaboration and a curiosity towards new knowledge becomes important features of the modern architect.
Keywords: Regenerative design, Bioremedation, Eutrophication, Marine resources, Building materials